Structural design for pressure-and temperature-resistant buildings - Sonthirongnachai, Boonchai; Petchsasithon, Arthit (My University, 2019)
Loads from explosions differ from seismic and wind loads due to their greater severity, continuity, rapidity, and thermal extremity. That is, explosions cause massive structural damage by exposing surrounding structures to extremely high pressure and temperature. Thus, structures at risk of explosive damage must be stronger than typical buildings in withstanding both ordinary loads and the additional pressure and temperature loads caused. Explosion-resistant structures are required in the petrochemical industry, explosive armories, power stations, and gas storage facilities, among others. This study aims to examine the structural performance of a building subject to three types of loads: (1) the pressure of 300 bars, (2) the temperature of 300 °C, and (3) the pressure of 300 bars combined with the temperature of 300 °C. The research analyzes three primary reinforced structures, namely columns, beams, and slabs, in terms of the parameters resulting from each scenario to determine a set of criteria for designing the structural components of explosion-resistant buildings.
Keywords: Pressure load; Pressure-and temperature-resistant buildings; Temperature load